The Strategy of Continuous Professional Development Program for Elementary School Teachers on Pedagogical Competencies - Hikmawati Risa; Nurjannah; Faisal Madani (Elementary Teacher Education Program, Majalengka University, 2024)
Professional teachers participate in creating a fun and meaningful learning process that fosters a love of learning in students. Continuous professional development provides space for students to grow and develop in learning through achieving pedagogical competence. However, the problem found is that the quality of interaction that supports students in learning by constructing knowledge has not been created and the planning and implementation of sustainable professional development has not been based on teacher needs, so that teacher involvement in working groups is relatively small. Therefore, this research aims to analyse strategies for developing sustainable professional programs and contribution programs to the pedagogical competence of SDIT Al Kawaakib teachers. The research method used is qualitative with a case study approach. Data collection was carried out through interviews, observation and documentation. The informants in this research were school principals and teachers. The research findings obtained are that continuous professional development contributes to teachers' pedagogical competence and strategies carried out through learning communities with collaborative and participatory work approaches related to learning practices to stimulate teachers' reflective abilities. The next recommendation that can be made is a sustainable professional development strategy that can contribute to pedagogical competence through teacher scientific work to determine the effectiveness of learning.